Crystallization and mechanical behavior of semi-crystalline polyethylene. (9th December 2021) - Yan, Z; Zaoui, A; Zaïri, F
Abstract: Molecular dynamics simulations are employed to study the crystallinity and mechanical properties of multi-chain polyethylene systems. Results show that structural composition (length and number of chains) and temperature lead to different crystallinity, which are obtained by using two general measurement methods, namely chain orientation and global order. The semi-crystalline polyethylene systems are deformed under various mechanical loading modes and at different temperatures representing different polymer states. The stretching temperature and structural composition have a strong influence on the mechanical properties, including elastic modulus, yield stress and inelastic mechanisms. The orientation crystallization caused by the heat treatment stage induces a significant directional effect on the different parts of the large-strain stress-strain response. Besides, the competition of the two main inelastic deformation mechanisms, namely shear yielding and cavitation damage, are revealed during the course of stretching.